WIND ANALYSIS OF TALL BUILDING IN DUHOK CITY USING COMPUTATIONAL FLUID DYNAMIC (CFD) - SAADULLAH, SHIREEN T.; HAIDO, JAMES H. (Journal of Duhok University, 2017)
Present article is devoted to study wind flow around concrete buildings. Computational fluid dynamic (CFD) model was performed in three dimensional (3D) commercial packages ANSYS CFX 14.0. utilizing finite volume technique to predict the wind pressures on tall buildings using specific boundary conditions. RNG k-ε turbulence model was used in the program to consider the wind turbulence. Current numerical approach was verified by comparison the outcomes with experimental wind tunnel tests. This valid CFD model was applied in the simulation of the wind analysis for Rixos Hotel which is located in Duhok City, Iraq. Analysis outputs of Rixos building were compared to those calculated by some international building codes; reasonable agreement was observed with using ASCE 2010 code. It is concluded that the stagnation point at which the wind streamline velocity comes to rest is located at 2/3 of the building height above the ground surface.